KOMPETENSI MENULIS DALAM PENGEMBANGAN LITERASI ULAMA DAYAH ACEH KONTEMPORER (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2019)
Acehnese scholars produced a lot of work during the periode of 18-19th century AD.The results of their work can still be read and used as a reference to the 21th century, thus it gives an indication that the scholars of Aceh in the past relatively productive in writing. However, in the 20th century, the tradition of writing among dayah scholars is hardly found so that it raises a question related to the involvement of scholars in writing and the competences of dayah scholars in Aceh, particularly in the North East, and South West region of Aceh.This study was performed in a qualitative approach utilizing purposive sampling techninque. The subjects of the study included dayah leaders, head of Islamic scholar assembly, head of Shari'a and dayah empowerment, head of the Office of Religious Affairs, and the administrators of Mubahatsah of dayah scholar in West Aceh district. Data was collected through observation, interviews and document analysis. All information obtained was analysed through reduction step, display, and verification. The study found that the writing competence of the dayah scholars was still relatively 'low' and most of them hardly ever participated in learning and training related to academic writing. Hence, the researchers concluded that the dayah scholars in West Aceh have no competence in writing and it might be argued. In addition, among dayah scholars, there was a perception that the classic holy books (the yellow holy books) was the most perfect and authentic reference which. Therefore, there is no motivation to write or to produce work unless there are few people with self-taught ability to analyze the context of the today’s issues.